2011
DOI: 10.1002/jssc.201100650
|View full text |Cite
|
Sign up to set email alerts
|

Use of capillary electrophoresis with chemiluminescence detection for sensitive determination of homocysteine

Abstract: A sensitive capillary electrophoresis (CE) method with chemiluminescence (CL) detection was developed for the determination of homocysteine (HCys) in human plasma. In this work, N-(4-aminobutyl)-N-ethylisoluminol was used as tagging reagent to label the analyte for achieving high assay sensitivity. N-(4-Aminobutyl)-N-ethylisoluminol-tagged HCys after CE separation reacted with hydrogen peroxide in the presence of horseradish peroxidase, producing CL emission. Experimental conditions for labeling analyte, CE se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To elucidate the function of Hcy and Cys in biochemical processes and clinical practice, their identication and accurate measurement are essential. In recent years, several CE procedures have been applied [7][8][9][10][11][12] to evaluate Hcy and thiols in general, in body uids. Many electrophoretic procedures for thiols and similar or related compounds have employed LIF 5,[13][14][15][16][17][18][19][20] detection but also UV [21][22][23][24][25][26] and amperometric [27][28][29][30][31] detection have been proposed with success.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the function of Hcy and Cys in biochemical processes and clinical practice, their identication and accurate measurement are essential. In recent years, several CE procedures have been applied [7][8][9][10][11][12] to evaluate Hcy and thiols in general, in body uids. Many electrophoretic procedures for thiols and similar or related compounds have employed LIF 5,[13][14][15][16][17][18][19][20] detection but also UV [21][22][23][24][25][26] and amperometric [27][28][29][30][31] detection have been proposed with success.…”
Section: Introductionmentioning
confidence: 99%
“…CE is a powerful separation tool with the advantage of high‐efficiency separation, short analysis times and low sample loading , and studies have shown that CE is a versatile platform for enzyme study and inhibitor screening . Chenet et al developed a CE method for the screening of 20 proteasome inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…CE–CL detection method has also been applied to amino acid , PCR product , saccharide , organic small molecule , and metal ion analysis.…”
Section: Applicationsmentioning
confidence: 99%